Friedreich’s Ataxia-A Case Report - Tahreem Muntaha , Saman Saleem , Sana Qurban , Mawra Noor, Tahreem Muntaha , Saman Saleem , Sana Qurban , Mawra Noor (Students' Supplement of Journal of Rawalpindi Medical College, 2022)
Friedrich’s ataxia (FA) is an autosomal recessive disorder. It is the most common cause of inherited ataxia. It affects approximately 1-2 persons per 100,000 population.1 It occurs due to a mutation that results in the homozygous expansion of Guanosine Adenine Adenine trinucleotide (GAAT) repeat units in intron 1 of FRATAXIN gene in chromosome 9.2,3 Its pathophysiology can be explained by “Dying back phenomenon”; progressive damage to axons with ultimate neuronal death, mostly in spinal cord but can also involve cranial nerves VII, X and XII.4 Apart from neurological manifestations cardiomyopathy5,6 and endocrine pathologies also occur which contribute to a worsened prognosis of the disease i.e. within 15-20 years of onset, patient becomes wheel chair bound and has a shortened life expectancy. Cardiac pathologies are the most common cause of death in Friedreich’s ataxia.2